GREENHOUSE GAS EMISSIONS INVENTORIES AS A TOOL THAT SUPPORTS THE CLIMATE CHANGE LOCAL AGENDA: SAN JOSE EXPERIENCE - Herrera-Murillo, Jorge; Rojas-Marín, José Félix; Quirós-Fallas, Andrea; Balma-Montero, Carolina; Anchía-Leitón, Deivis (Revista Geográfica de América Central., 2017)
San José greenhouse gas emissions were estimated applying a methodological approach adapted from the IPCC guidelines and the GHG protocol for cities such as basic input to guide the local agenda on climate change. In total during the year 2011, 820 295 tons of equivalent CO2 were generated. In order of importance, mobile sources accounted for 84.7 % of emissions, followed by electricity consumption in the residential sector as a whole (7.7%) and fixed sources of industrial sector (1.4%). Direct emissions contributed to 90.9 % of the inventory while indirect (Scope 2 and 3) represent 9.1%. On average, each home generates about 0.41 tons CO2 eq / year; however, this indicator ranges from 0.66 tons of CO2 eq / year in Uruca to 0.33 tons of CO2 eq / year in Hatillo.